2020
DOI: 10.1101/2020.04.27.20081737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 spreading in Rio de Janeiro, Brazil: do the policies of social isolation really work?

Abstract: In this case, we observe a distinct behavior: a sub-exponential growth. In order to capture this change in the behavior of the evolution of the confirmed cases, we consider the implementation of isolation policies. The modified model agrees well with data. Finally, we consider the relaxation of such policies, and discuss about the ideal period of time to release people to return to their activities.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 48 publications
0
43
0
3
Order By: Relevance
“…For this reason, the present study analyzes the spread in this state, as well as in the country as a whole, in order to assess the particular characteristics of the pandemic at those different spatial scales. Extensive research for the spread of COVID-19 in BR with multiple perspectives has been reported, e.g., [28,27,29,30,31,32]. The present work takes into account factors that are predominant in many underdeveloped countries, such as the current limited testing capacity and the policy to test only severely ill hospitalized individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the present study analyzes the spread in this state, as well as in the country as a whole, in order to assess the particular characteristics of the pandemic at those different spatial scales. Extensive research for the spread of COVID-19 in BR with multiple perspectives has been reported, e.g., [28,27,29,30,31,32]. The present work takes into account factors that are predominant in many underdeveloped countries, such as the current limited testing capacity and the policy to test only severely ill hospitalized individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters, as well as model initial conditions, were set based on available information on COVID-19 (see the SM for more details). Our simulation forecasts that the peak of active cases occurred on July 28, 2020 (95% CI: [26][27][28][29] and July 3, 2020 (95% CI: 2-4) for BR and RJ, respectively. This difference can be explained due to the discrepancy of the spatial scale, and the way the disease has spread along with the different Brazilian locations, considering, for instance, different political measures taken and the social and demographic structure of each Brazilian locality [33].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, mathematical models have played an important role in understanding the dynamics of infectious diseases and in designing health policy strategies [3] , [4] , [5] , [6] , [7] . In fact, these models have been used extensively to investigate different types of infection dynamics such as influenza A [8] , Zika [9] , Ebola [10] , SARS [11] , [12] , MERS [13] , [14] , and, more recently, COVID-19 [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several compartmental models have been proposed for COVID-19 spread in different regions of the world: see, e.g., Contreras (2020) for a multi-group SEIRA model; Maier and Brockmann (2020) for the impact of effective containment in the growth of confirmed cases in the outbreak in China; Crokidakis (2020) for a COVID-19 spread study in Brazil; Mohsen et al. (2020) for a COVID-19 model that considers media coverage effects; Hattaf and Yousfi (2020) for a within-host model, which describes the interactions between SARS-CoV-2, host pulmonary epithelial cells, and cytotoxic T lymphocyte cells; and Zine et al.…”
Section: Introductionmentioning
confidence: 99%